Warty Dyskeratoma with involvement of multiple hair follicles in a dog - Silva, Luiz Augusto Santana; Conti, Luiza Cesar (Brazilian Journal of Veterinary Pathology, 2023)
The warty dyskeratoma is a neoplasm of follicular origin, with uncommon incidence in veterinary medicine, and benign biological behavior. An excisional biopsy sample was received from a dog, female, Shih Tzu, 12 years old, from the left axillary region. Grossly, after section, green and friable multifocal areas were identified, streaked by solid white areas. Microscopically, the analysis revealed multifocal cystic structures, lined by stratified epithelium, with basal area including villous epithelial projections, toward the dermis, and the luminal region featured acantholysis and dyskeratosis, as well as parakeratosis. Those findings were compatible with a warty dyskeratoma affecting multiple hair follicles, thus being the first case report in veterinary medicine with such this unique pattern. Up to now, the literature encompassed only human medicine. This report, besides collaborating to the description of a rare presentation of an uncommon neoplasm, also contributes with new information found for epidemiological studies of this tumor.